The clinical and anatomopathological and histologic alterations produced by the natural and accidental poisoning by sodic salinomycin in peccaries (Tayassu tajacu) - Ribeiro, Vânia Maria França; Santos, Francisco Glauco de Araújo (Brazilian Journal of Veterinary Medicine, 2016)
ABSTRACT. Ribeiro V.M.F. & Santos F.G.A. [The clinical and anatomopathological and histologic alterations produced by the natural and accidental poisoning by sodic salinomycin in peccaries (Tayassu tajacu).] Alterações clínicas e anatomopatológicas produzidas por intoxicação acidental com salinomicina sódica em catetos (Tayassu tajacu). Revista Brasileira de Medicina Veterinária, 38(1):69-72, 2016. Laboratório de Apoio à Vida Silvestre, Centro de Ciências Biológicas e da Natureza, Universidade Federal do Acre, Campus Universitário Rio Branco, Rodovia BR-364 Km 4, Rio Branco, AC 69920-900, Brazil. E-mail: vania.rib@uol.com.br Sodic Salinomycin is a polyester monocarboxylic antibiotic of the ionophore group. It has antibacterial and anticoccidial properties. The intoxication for ionophore antibiotics happens when there is ingestion of high doses of the drug for mistakes of calculations or contamination of rations. That work had the aims to describe the clinical and anatomopathological and histological alterations produced by the natural and accidental intoxication by sodic salinomycin (Coxystar 12% granular®) in peccaries (Tayassu tajacu). 37 animals were submitted accidentally to the ingestion ad libitum of sodic salinomycin, in the farm of wild animals “Caboclinho da Mata”, located in Experimental Finance “Catuaba” belonging to the Federal University of Acre. Of the individuals that consumed the salinomycin, 14 died in the period of 15 days after the ingestion. It was observed in the animals: anorexia, motor incordination, staggering pace, asthenia, ventral decubitus and death. One of the animals that came to death was submitted to the necropsy. Liver fragments and cardiac muscle were collected, fastened in formaldehyde to 10% and processed, and embedded in paraffin, cut at a nominal thickness of 4 µm, and stained with hematoxylin and eosin for histopathological examination. Macroscopically, indicative lesions of degenerative process were observed, in the liver, where this presented pattern evident lobular and congestion. In the heart, a bulging was observed, with dilation of the right camera, subepicardials and miocardials hemorrhages. Microscopically, in the liver, the lesions were distributed in a diffuse way by the parenchyma of the organ, with ectasia of the centrilobulares veins and hepatocytes vacuolateds. These vacuolizations had forms and varied sizes, as well as dilation of the sinusóides and discreet megalocitose, and in the heart muscle, besides vascular lesions, characterized by hiperemia and edema, any lesion was not observed in the fibers. Intoxications for salinomycin were already registered in swine, caprine, bovine, cats, alpacas, turkeys, rabbits, equine and chinchillas. The anamnesis and the clinical symptomatology presented by the animals that ingested natural and accidentally the sodic salinomycin, going to death, as well as the discoveries macro and microscopic they suggest a diagnosis of acute and sub-acute phase intoxication for antibiotic ionóforo, being these the first cases told in peccaries.